Analisis dan Perancangan Aplikasi Website Penjualan pada Toko Sembako dan Sayuran Mommy Market - Raden Andhika Prihestira; Jessica Ausilia Afriyani (Asosiasi Dosen Muda Indonesia, 2025)
This study aims to analyze and design a shopping site application at the Mommy Market Store located in the North Bekasi City area, and to implement the design results into a computer application program. So that the time for administrative work in serving consumers or buyers, so that administrative activities, especially shop buying and selling transactions, become faster and the data collection process becomes more organized. The system development method used in the study is waterfall. While the system modeling uses object orientation modeling or UML. The programming language used is PHP CodeIgniter and javascript, while for the database application, using MySQL The results of this study are expected to make the service at the Mommy Market Store more efficient, effective and well-structured. In addition, it can also help the performance of the store in handling sales data and inventory of goods at the store.